COMPLEX APPROACH TO ASSESSMENT OF CONDITION SEVERITY IN PATIENTS WITH PYOINFLAMMATORY ODONTOGENOUS DISEASES - Yu. A. Shcherbuk; D. Yu. Madai; A. Yu. Shcherbuk; Yu. A. Garmashov; O. D. Madai; E. A. Nikitina (Вестник хирургии имени И.И. Грекова)
Dynamics of mean value indices and mean dispersion doesn’t exclude the feedback (Mayanskiy D. N., 2008) in process of study the disease according to cooperative processes using system leukocyte-monocyte-lymphocyte (L+M+LM). The authors investigated a dynamic balance between these cell substratums and collagen formation. Acute inflammatory processes in tissues of maxillofacial area accompanied by leukemoid response of peripheral blood in the form of leukocytosis (10·10⁹-15·10⁹/l and more). The authors completely agree with the opinion of M. M.Solov’yov (2012) and N. K. Artyushenko (2008) that mechanism of this reaction is associated with both the leukocyte redistribution in the inflammation zone and with changes of hematopoietic rostock which aimed to balance the affected compensatory mechanisms of nonspecific resistance.